KAJIAN LANSKAP BUDAYA SUKU MATABESI DI KABUPATEN BELU NUSA TENGGARA TIMUR - Pareira, Novica Christiani; Nuraini, Nuraini; Setyabudi, Irawan (Fakultas Pertanian, 2019)
The Matabesi tribe is the oldest tribe on the island of Timor which is located in the Umanen Fatuketi Village, Atambua Barat District, Belu Regency, East Nusa Tenggara Province. The life of the people of the Matabesi tribe is still dependent on nature, for example the use of reeds as material for roofing. The purpose of this study was to identify the characteristics of the Matabesi tribe's cultural landscape, and analyze the sustainability of the Matabesi tribe's cultural landscape. The research method is carried out qualitatively by describing the condition of architecture, cultural landscape, and activities that occur in the Matabesi Tribe area. The results of the study showed that the physical, biophysical, socio-cultural and economic values found in the Matabesi Tribe region are still well organized, and there are elements forming a landscape, includingUma, Aitos, Fatuklulik, Sadan Sri Fo’o Lakaan, We matan and Rate meo. Suku Matabesi merupakan suku tertua di Pulau Timor yang terletak di Kelurahan Umanen Fatuketi, Kecamatan Atambua Barat, Kabupaten Belu, Provinsi Nusa Tenggara Timur. Kehidupan masyarakat Suku Matabesi ini masih tergantung pada alam, contohnya pada penggunaan alang- alang sebagai bahan atap rumah. Tujuan penelitian ini adalah mengidentifikasi karakteristik lanskap budaya Suku Matabesi, dan menganalisis keberlanjutan lanskap budaya Suku Matabesi. Metode penelitian dilakukan secara kualitatif dengan mendeskripsikan kondisi arsitektur, lanskap budaya, dan aktivitas yang terjadi pada kawasan Suku Matabesi. Dari hasil penelitian didapatkan hasil bahwa nilai-nilai fisik, biofisik, sosial budaya dan ekonomi yang terdapat pada kawasan Suku Matabesi masih tertata dengan baik, dan terdapat elemen pembentuk lanskap antara lain Uma, Aitos, Fatuklulik, Sadan Sri Fo’o Lakaan, We matan, dan Ratemeo.